1985
DOI: 10.1159/000183340
|View full text |Cite
|
Sign up to set email alerts
|

A New Plethysmograph for Detecting Arterial Pulse Waves in Rat Tail

Abstract: A new plethysmograph for detecting arterial pulse waves in the rat tail is described. With the objective of indirectly measuring the arterial blood pressure in small animal tails an easy-to-build plethysmographic chamber is presented. Essentially in this apparatus the atmospheric air insulated in the chamber is used as the transmitter of the volume changes caused by the arterial flow. By this methodology details of the pulse wave morphology are clearly visible, including the dicrotic notch. It is demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…However, in this paper as well as in others [8,21,25,27] close inspection of some representative tracings does show a lower BP value during Def. On the contrary, our measurements coincide with the paper of Martinelli et al [5] who reported a significant decrease of 11 mmHg for the Def cycle, nearly double than the one we found in normotensive rats. This difference can probably be accounted for by their method of pulse detection, a water plethysmograph, which probably implied a longer Inf-Def interval than in our experiments.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, in this paper as well as in others [8,21,25,27] close inspection of some representative tracings does show a lower BP value during Def. On the contrary, our measurements coincide with the paper of Martinelli et al [5] who reported a significant decrease of 11 mmHg for the Def cycle, nearly double than the one we found in normotensive rats. This difference can probably be accounted for by their method of pulse detection, a water plethysmograph, which probably implied a longer Inf-Def interval than in our experiments.…”
Section: Discussionsupporting
confidence: 91%
“…They also found that the values during the Inf cycle are in closer agreement with the intraarterial measurements than the Def ones. These data are coincident with our own results, but the authors did not provide any hypothesis and/or pursue further experiments to explain the difference between Inf and Def values [5].…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, the commonly used tailcuff methods for measuring systolic blood pressure (SBP) in the rat, which employ plethysmography 13 or Doppler ultrasonic flowmeter, 4 require preheating of the animals to enhance the amplitude of pulsation in order to record the pulse signals. Such a maneuver can artificially increase SBP 3 ' 6 and, therefore, can lead to less accurate determination of SBP. The photoelectric sensor technique, 7 "" as described by Yen et al 10 and studied by Bunag and Butterfield," does not require preheating, but a high ambient temperature is needed for reliable measurements of SBP.…”
mentioning
confidence: 99%